Safety of dairy products in the light of consumer surveys - Aneta Zofia Dąbrowska; Dorota Zajkowska; Adam Więk; Sylwester Rybaczek (Kazimierz Wielki University, 2017)
The aim of the reported study was to determine the level of knowledge and awareness of consumers regarding the safety of dairy products. The perception of dairy products safety was evaluated through diagnostic survey among 206 respondents from the Warmia and Mazury Province and the Mazowieckie Province selected for the survey with the convenient sampling method. Obtained results demonstrate that consumers' knowledge about safety of these products is scanty, but show also that the safety level perceived by consumers is unsatisfactory. It would, therefore, be advisable to undertake actions aimed at increasing consumer awareness concerning the safety of dairy products.